1998
DOI: 10.1016/s0896-6273(00)80482-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure and Function of an A Kinase Anchoring Protein Associated with Calcium Channels

Abstract: Rapid, voltage-dependent potentiation of skeletal muscle L-type calcium channels requires phosphorylation by cAMP-dependent protein kinase (PKA) anchored via an A kinase anchoring protein (AKAP). Here we report the isolation, primary sequence determination, and functional characterization of AKAP15, a lipid-anchored protein of 81 amino acid residues with a single amphipathic helix that binds PKA. AKAP15 colocalizes with L-type calcium channels in transverse tubules and is associated with L-type calcium channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
164
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(171 citation statements)
references
References 40 publications
7
164
0
Order By: Relevance
“…We provide a direct validation of the negative feedback model suggested by such a molecular organization and prove that it applies to subsarcolemmal cAMP dynamics. Dodge et al (50) only found a modest PDE activity associated with AKAP15/18, the AKAP thought to associate with L-type Ca 2ϩ channels at the membrane (62,63). This fits well with the fact that limited cAMP increases induced by ISO fully activate I Ca,L , and suggests that the feedback loop identified here is essentially useful to prevent broadcast of cAMP outside of microdomains where it is needed (8,14).…”
Section: Discussionsupporting
confidence: 74%
“…We provide a direct validation of the negative feedback model suggested by such a molecular organization and prove that it applies to subsarcolemmal cAMP dynamics. Dodge et al (50) only found a modest PDE activity associated with AKAP15/18, the AKAP thought to associate with L-type Ca 2ϩ channels at the membrane (62,63). This fits well with the fact that limited cAMP increases induced by ISO fully activate I Ca,L , and suggests that the feedback loop identified here is essentially useful to prevent broadcast of cAMP outside of microdomains where it is needed (8,14).…”
Section: Discussionsupporting
confidence: 74%
“…The resulting antibody was affinity-purified on peptide columns as described (45), and specificity of the antibody was confirmed by immunoblotting. Anti-AKAP15 antibodies and RII-biotin protein were prepared as described (39). Anti-RII␣ antibody against the type II␣ regulatory subunit of PKA was kindly provided by G. Stanley McKnight (University of Washington).…”
Section: Methodsmentioning
confidence: 99%
“…A candidate for this is the receptor-activated cAMP-dependent protein-kinase (PKA) cascade. It has been shown that activation of PKA by stimulation with acetylcholine increases ADP-ribosyl cyclase activity in chromaffin cells [31], facilitates CD38 expression in Jurkat T cells [32] and enhances L-type VACC activity targeted by the PKA-anchoring protein [33].…”
Section: Scheme 1 Models For Reciprocal Interactions Between Ryrs Andmentioning
confidence: 99%